The search for generic manufacturing strategies in the UK engineering industry - Sweeney, Mike T.; Szwejczewski, Marek (Cranfield University, 1996)
The search for generic manufacturing strategies has been attempted previously using the American and the European Manufacturing Futures survey data. This paper details the results of a study using manufacturing strategy and performance data submitted by 120 competitors for the 1993 and 1994 UK Best Factory Award. The research method used was the same as that applied by the previous researchers of this subject. This was to carry out a cluster analysis of the rankings of emphasis to be given to the improvement of six competitive capabilities during a two year period following completion of the questionnaire. Only data from UK engineering companies were used for this analysis. The study findings are similar to those of the previous American study but add to them. Four distinct clusters of different competitive capabilities were observed. The distinguishing competitive capability of each cluster was found to be consistent with those detailed in a previously published theoretical framework that linked competitive capabilities with generic manufacturing strategy types.